Estudos funcionais de inibidores de cisteíno peptidases da cana-de-açúcar e caracterização de uma cisteíno peptidase de Sphenophorus levis, uma importante praga da cultura canavieira - Dellamano, Marcia (2009)
Cystatins are proteins that inhibit specifically cysteine peptidases. The Canecystatin 1 gene which codifies a protein containing 106 amino acids residues was identified in sugarcane and possesses significant similarity with Oryzacystatin, a cystatin from rice. In order to obtain a cystatin with improved activity, direct evolution experiments were carried out. A DNA shuffling library was constructed using these two cystatins. One clone named A10PL3 obtained from these shuffled cystatins was selected, expressed in E.coli, purified and an analyzed by activity assays. These results showed that the activity of hybrid protein A10PL3 increased, in particular regarding its inhibitory activity on cathepsin B compared with its two precursors. The present study aimed to revert the changes of individual clone A10PL3 through site-directed mutations, generating three mutant cystatins: Mutant I (Thr17Ile), Mutant II (Gln 84Leu) and Mutant III (Thr17Ile); (Gln84Leu). Assays for inhibitory activity against the human cathepsins B and L were performed. Structural studies were also made by means of molecular modeling of proteins by homology that were enabled to understand the molecular mechanisms related to improvement of the inhibitory activity of these cystatins. These studies therefore corroborate with the observed data previously which demonstrated the improvement of specific protein A10PL3 in cathepsin B inhibition (Ki 16 nM) in relation to their parents. The mutants I, II and III, did not present improvement in inhibitory activity against cathepsin B. The structural studies revealed that the mutations performed on cystatin A10PL3 destabilized the hydrophobic core making it more flexible, thus increasing the inhibitory activity on cathepsin B. The absence of interactions underlying the hydrophobic core resulted in a trend of lower solubility, probably due to their inability to adopt a compact formation, which resulted in the exposure of some residues which are part of that core, which can lead to aggregation and also contribute to increasing the flexibility of cystatin, influencing their inhibitory activity.